THE ROLE OF EDUCATION LEVEL IN INTIMATE PARTNER VIOLENCE AMONG PREGNANT WOMEN IN RURAL INDONESIA - Laksono, Agung Dwi; Wulandari, Ratna Dwi; Matahari, Ratu (Jurnal Keperawatan Indonesia Timur (East Indonesian Nursing Journal), 2023)
Background: Pregnancy is a physically and psychologically vulnerable period, and women with lower education tend to be more psychologically vulnerable. Objective: The study analyzes the role of education in intimate partner violence among pregnant women in rural Indonesia. Methods: The cross-sectional study uses secondary data from the 2017 Indonesian Demographic and Health Survey. The study employed 1,337 pregnant women who had partners in rural Indonesia. Apart from intimate partner violence as the dependent variable, this study involves education, age, marital, employment, wealth, parity, owning a house, and recent sexual activity as the independent variable. In the final stage, the author calculated the role using multivariable binary logistic regression. Results: The results show pregnant women with the education level in the no education category had 2.479 times the possibility of pregnant women with a higher education level experiencing intimate partner violence (AOR 2.479; 95% CI 1.158-5.305). Pregnant women with a primary education level have 1.650 times greater odds than those with a higher education level of experiencing intimate partner violence (AOR 1.650; 95% CI 1.059-2.571). On the other hand, pregnant women with a secondary education level have 1.682 times greater odds of experiencing intimate partner violence than those with a higher education level (AOR 1.682; 95% CI 1.094-2.585). Apart from education level, wealth status and the variable of owning a house are related to intimate partner violence among pregnant women in rural Indonesia. Conclusion: The study concluded that education level has a role in intimate partner violence in rural Indonesia.